Critical issues on Islamic banking and financial markets : Islamic economics, banking and finance, investments, Takaful and financial planning - Rosly, Saiful Azhar (Dinamas Publishing, 2005)
This book examines the principles and practices ofIslamic banking and financial markets, particularly from the Malaysian experience. The main objective of Islamic financial system is to govern the flow of funds from the surplus sector to the deficit sector and it does so to promote justice ('adalah). That is, by adhering to Shariah principles and achieving efficiency - doing the right thing and doing it right, public and private interest interests are can both be protected. By doing so, the legal and moral dimensions of product design and development are now equally important. In this way halal status should not discount how Islamic products affects general economic activities. It means that Shariah advisors should not only approve Shariah complaint products along the juristic plane but dutifully consider how the products can affect income disparities and poverty, economic stability and growth. For this reason, the principle of risktaking (ghorm) and the principle of work (kasb) and the principle of liability, accountability, responsibility (daman) are paramount in determining Shariah legitimacy of profits and earnings derived from Islamic financial transactions. Risk (ghorm), work (kasbh) and liability (daman) constitute the essence of trading and commerce (ai-bay') the Holy Quran has enjoined over usury (riba). By risk, it means allowing capital to depreciate and appreciate as dictated by the market forces. By work, it refers to value-additions namely, knowledge and skills imparted into the business process. Liability means the responsibility each party must assume in the contract such as providing warranties on the goods and services sold. Based on these principles ofrisk, work and responsibility, also known as the principle of equivalent countervalue ('iwad), the ethical and moral dimension of Islamic fmancial transactions can be realized and thus promote the sense of justice the Quran attempts to convey. It helps people take a second-look at financial products that have received Shariah compliant status and help control potential duplication of interestbearing products bearing the Islamic label.